Pengaruh Penerapan Akuntansi, Pemahaman Perpajakan, dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak UMKM Berbasis Media Electronik: Studi Kasus di Kecamatan Alang-Alang Lebar Palembang - Antika Ayu Anggraini; Harsi Romli; Vhika Meiriasari (ManBiz: Journal of Management and Business, 2024)
This research aims to determine the influence of accounting implementation, understanding of taxation, and taxpayer awareness on electronic media-based MSME taxpayer compliance. This research was conducted in Alang-Alang Lebar District, Palembang, totaling 73 respondents. The type of research used is quantitative research by distributing questionnaires. Sampling used convenience sampling. The data source in this research is primary data based on the results of the t test showing that with a sig value that the Application of Accounting (X1), Understanding of Taxation (X2) and Taxpayer Awareness (X3), on Electronic Media Based MSME Taxpayer Compliance (Y) because t count > t table or 3.026 > 1.99394,1.534 < 1.99394 and 2.692 > 1.99394 with significant 0.003 < 0.05, 0.130 > 0.05 and 0.009 < 0.05 which means the Accounting Implementation variable has an influence and is significant on MSME Taxpayer Compliance Based on Electronic Media, Understanding of Taxation has no and no significant effect on Electronic Media Based MSME Taxpayer Compliance and Taxpayer Awareness has an influence and is significant on Electronic Media Based MSME Taxpayer Compliance. Then the results of the F test analysis show that the calculated F value > F table is 28.136 > 2.74 with a significant value of 0.00 < 0.05. This shows that the independent variables, namely Application of Accounting (X1), Understanding of Taxation (X2) and Taxpayer Awareness (X3) have a significant and influential effect on the dependent variable, namely Electronic Media-Based MSME Taxpayer Compliance (Y).